Are land rental markets responding to rising population pressures and land scarcity in Sub-Saharan Africa? - Abay, Kibrom A.; Chamberlin, Jordan; Berhane, Guush (Elsevier, 2021)
Although still at incipient stages in most areas, agricultural land markets in sub-Saharan Africa (SSA) are growing rapidly. While the literature on the region’s land markets is expanding, there has been little attention thus far paid to the drivers of land rental prices. We know quite little about whether and how land markets and land contracts respond to meso-scale factors such as spatial variations in land abundance, or to micro-level factors, such as household land endowments. In this paper, we study the response of land markets, and hence whether land market participation trends and land market rental prices respond to land scarcity. Drawing on nationally representative household survey data from Ethiopia, Malawi and Tanzania, which represent a large range of relative land scarcity conditions, we examine how land markets are responding to cross-sectional variations in land scarcity in terms of rental market participation rates, prices, and contractual arrangements. In all three countries, we document that rental market participation rates and land rental prices increase with land scarcity. We also find that land rental prices per hectare decrease with plot size. These land market responses and their heterogeneities have important implications for land distribution and land market policies.